Women’s terrorism: criminological characteristics, causes and ways of prevention - Ткачова, Олена Вікторівна (Theory and practice of jurisprudence, 2019)
The article deals with the issue of women’s terrorism. The reasons and motives from which women commit suicide attacks are considered, the causes of terrorism are listed separately and their classification is given. It is stated that the causes of crimes related to terrorism are divided into the following categories: socio-economic, legal, political, socio-psychological and organizational-managerial. Attention is paid to international and national acts in the field of counter-terrorism, based on the requirements of which the fight against this negative phenomenon is being conducted. Despite the relevance of the identified problem, it is very difficult to solve it, since information on women-kamikaze is extremely small. In addition, there was almost no research on their status in terrorist organizations, methods of recruiting and psychological treatment, etc., which is quite logical, since terrorist groups are closed organizations and their activities are concealed. Hopefully, the raised issues will be the subject of a separate study, because terrorism forms and puts a sense of fear in society, and a large number of terrorist acts committed in the world intensifies it, which, in turn, suppresses the positive activity of the individual. Moreover, terrorism can lead and, as practice shows, actually leads to the curtailment of state, legal guarantees and freedoms of the individual, since it forces States to take countermeasures that are not always consistent with the rule of law. Despite this, the resistance and the fight against terrorism, especially women’s, is not only necessary, but also necessary